Modelling and simulation of impedance-based damage monitoring of structures - Djemana, Mohamed; Hrairi, Meftah (DAAAM INTERNATIONAL VIENNA, 2016)
Electromechanical impedance (EMI) based monitoring techniques are successfully in use in current engineering structures. With the help of piezoelectric sensors, the EMI technique is used for monitoring the health of such structures. Generally, potential damage to the host structure is detected by examining the EMI signature and identifying changes in that unique signature. Since this technique has the potential to offer greater safety and reliability while lowering maintenance costs, it is becoming increasingly popular. This paper investigates the use of finite element method (FEM) to simulate the electro-mechanical impedance technique. A numerical analysis of simple models, such as free piezoelectric patches of various shapes and thicknesses is used to comprehend the fundamentals of this technique. Then, studies on different parts of the structure are conducted to find the effect on the output of system when both damage and loading co-exist, and investigate the effect of temperature for structural health monitoring based on EMI. The simulation results are then compared to experimental data and a very good agreement is observed.